Critical Role of Surface Properties in Passive Interstitial Fluid Extraction Using Polymeric Hollow Microneedles for Wearable Diagnostics - Ipek Atay; Emel Yilgör; Gürdeniz Neşer; Taher Abbasiasl; M. Baris Yagci; Iskender Yilgör; Levent Beker (Advanced Materials Interfaces, 2025)
Abstract Efficient sampling of dermal interstitial fluid (ISF) is essential for continuous monitoring of biomarkers for early detection and management of chronic diseases. Transdermal ISF extraction using microneedles gained popularity due to their minimally invasive nature and efficient sampling capabilities. Among various ISF extraction modalities, passive extraction with hollow polymeric microneedles (HMN) stands out as an efficient, economical and user‐friendly alternative that eliminates the need for external pumps or complex recovery processes. As passive HMN extraction relies on capillary action, influence of surface morphology and wettability of microchannels are investigated. In vitro ISF absorption capacities of HMNs fabricated by laser machining using polylactic acid (PLA), polymethyl methacrylate (PMMA) and polycarbonate (PC) are investigated. Microchannels are created on needle tips through micromachining with a 355 nm laser. Surface roughness induced by laser exposure is most prominent in PLA HMNs, which exhibited an absorption rate of 0.02 mg min−1 per needle at an insertion force of 1.4 N per needle, while PMMA and PC‐based HMNs showed rates of 0.01 mg min−1 at 1.9 and 2.3 N per needle respectively. These findings highlight the critical influence of surface properties in enhancing the capillary action during passive ISF extraction with polymeric HMNs, supporting their potential integration into next‐generation wearable biosensors.